Team Building Training To Improve Interpersonal Communication Among Operators At PT Komatsu Indonesia - Hapsari, Maharani Tyas Budi (Universitas Islam Negeri Raden Mas Said Surakarta, 2023)
Interpersonal communication is a core skill required by employees in every company. Effective interpersonal communication can be established with strong cooperation between employees. This research aimed to determine the effect of team building training in improving interpersonal communication among operators at PT Komatsu Indonesia. The mixed-method study combined qualitative (interviews and observations) and quantitative (quasi-experiment with one-group pretest-posttest design) approaches. Thirty-six operators were involved in the team building training. The team building training is effective in improving interpersonal skills in operators at PT Komatsu Indonesia (Z=-5.178, p<0.05). The results of this study can be the basis for companies or industries to improve employee interpersonal skills through training to minimize the occurrence of work accidents.